Calmodulin-Mediated Regulation of Gap Junction Channels - Camillo Peracchia (International Journal of Molecular Sciences, 2020)
Evidence that neighboring cells uncouple from each other as one dies surfaced in the late 19th century, but it took almost a century for scientists to start understanding the uncoupling mechanism (chemical gating). The role of cytosolic free calcium (Ca2+i) in cell−cell channel gating was first reported in the mid-sixties. In these studies, only micromolar [Ca2+]i were believed to affect gating—concentrations reachable only in cell death, which would discard Ca2+i as a fine modulator of cell coupling. More recently, however, numerous researchers, including us, have reported the effectiveness of nanomolar [Ca2+]i. Since connexins do not have high-affinity calcium sites, the effectiveness of nanomolar [Ca2+]i suggests the role of Ca-modulated proteins, with calmodulin (CaM) being most obvious. Indeed, in 1981 we first reported that a CaM-inhibitor prevents chemical gating. Since then, the CaM role in gating has been confirmed by studies that tested it with a variety of approaches such as treatments with CaM-inhibitors, inhibition of CaM expression, expression of CaM mutants, immunofluorescent co-localization of CaM and gap junctions, and binding of CaM to peptides mimicking connexin domains identified as CaM targets. Our gating model envisions Ca2+-CaM to directly gate the channels by acting as a plug (“Cork” gating model), and probably also by affecting connexin conformation.